Characteristics of mulching plastic film residue and its influencing factors in farmland of Gansu Province - Li, Mingkai; Liu, Yang; Zu, Na; Li Chongxiao; Zhou, Tao; Dai Lilan; Xiong Youcai; Cao, Jing (Journal of agricultural resources and environment, 2025)
为探讨甘肃省农田地膜污染现状和影响地膜残留的因素，本研究于2021年收集了甘肃省地膜残留定点监测站20个地县的400个监测点数据，采用问卷调查和采样调研相结合的方法对甘肃省各监测点地膜残留状况进行分析。结果表明：甘肃省农田地膜残留量在 2.80~146.50 kg·hm-2之间，平均值为 40.29 kg·hm-2，残留地膜的平均碎片质量为 11.44~79.61 mg·片-1，平均值为41.62 mg·片-1。影响地膜残留的因素较多且作用机制复杂，多元线性回归结果显示，种植地块面积、距村庄距离、灌溉条件、作物种类、覆膜年限、地膜厚度、回收方式等变量仅可解释地膜残留量37.10%的变化原因，其中地块面积、距村庄距离、作物种类、覆膜年限、回收方式会对地膜残留量产生显著的正向影响，而灌溉条件、地膜厚度对地膜残留量产生显著的负向影响。研究表明，对于地膜残留量高、碎片化程度低的地区，应当加强地膜回收监管力度；对于残留量和碎片化程度高的地区，应当寻求更加有效的地膜回收手段或地膜替代产品。目前的农田地膜回收机制虽然有效改善了地膜残留状况，但还需要研发从源头控制、过程管理到末端治理的集成创新技术，最终达到大幅度削减地膜残留的目的。Data from 400 monitoring points in 20 prefectures and counties of Gansu Province were collected in 2021, and a combination of questionnaires and sampling surveys was used to study the status of film residues in each monitoring point in Gansu Province, China to explore the current situation of agricultural film pollution and factors affecting film residues. The amount of film residue in Gansu Province ranged from 2.80 to 146.50 kg·hm-2, with an average value of 40.29 kg·hm-2, and the average fragmentatio